2008
DOI: 10.1002/chp.188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating conflicts of interest in research presented in CME venues

Abstract: While limited, by study design, this research detected subjectivity and variability in perceiving commercial bias within research findings presented in CME venues. Further study of these questions is required to guide the resolution of conflicts of interest in research and CME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…48,49 Conflict of interest should be declared for undergraduate and continuing education programs. 50 A nationally standardized certification process ascribed to by institutions offering continuing education programs similar to those serving other health professions would build trust for the profession.…”
Section: Domain 5-leadershipmentioning
confidence: 99%
“…48,49 Conflict of interest should be declared for undergraduate and continuing education programs. 50 A nationally standardized certification process ascribed to by institutions offering continuing education programs similar to those serving other health professions would build trust for the profession.…”
Section: Domain 5-leadershipmentioning
confidence: 99%
“…A previous study compared the rate of identification of commercial bias in CME professionals versus "trained physician peer reviewers" in CME presentations for family physicians. 3 Although interrater reliability was not calculated, the authors found that CME professionals were more likely to disagree on the presence of commercial bias than physician reviewers. When acknowledgments of potential conflicts were stated at the beginning of a presentation, neither group was more likely to perceive commercial bias~al-though knowledge of conflict of interest increased awareness FIGURE 1.…”
Section: Discussionmentioning
confidence: 98%